Answer

Verified

487.5k+ views

Hint:- Use the expansion of ${(1 + x)^n}$, where n is negative.

As, we are given with the series

$ \Rightarrow y = 2 + \dfrac{5}{{2!.3}} + \dfrac{{5.7}}{{3!{{.3}^2}}} + \dfrac{{5.7.9}}{{4!{{.3}^3}}} + ......$ (1)

So, the series at equation 1 can be written as,

$ \Rightarrow y = 1 + 1 + \dfrac{5}{{2!.3}} + \dfrac{{5.7}}{{3!{{.3}^2}}} + \dfrac{{5.7.9}}{{4!{{.3}^3}}} + ......{\text{ }}$ (2)

Now, we know that when we had to find the value of any typical series,

Then we try to manipulate the series into the expansion of a known function.

So, we had to manipulate the series at equation 2.

Above series can be manipulated as,

$ \Rightarrow y = 1 + \dfrac{3}{2}.\dfrac{2}{3} + \dfrac{{\dfrac{3}{2}.\dfrac{5}{2}}}{{2!}}.\dfrac{{{2^2}}}{{{3^2}}} + \dfrac{{\dfrac{3}{2}.\dfrac{5}{2}.\dfrac{7}{2}}}{{3!}}.\dfrac{{{2^3}}}{{{3^3}}} + \dfrac{{\dfrac{3}{2}.\dfrac{5}{2}.\dfrac{7}{2}.\dfrac{9}{2}}}{{4!}}.\dfrac{{{2^4}}}{{{3^4}}} + ......$ (3)

Now, as we know that the expansion of ${\left( {1 + x} \right)^n}$, where n is negative is,

$ \Rightarrow {(1 + x)^n} = 1 + \dfrac{n}{{1!}}x + \dfrac{{n(n - 1)}}{{2!}}{x^2} + \dfrac{{n(n - 1)(n - 2)}}{{3!}}{x^3} + ....$

As, we can see clearly that in the expansion of ${(1 + x)^n}$,

$ \Rightarrow $If we put $x = \dfrac{{ - 2}}{3}$ and ${\text{ }}n = \dfrac{{ - 3}}{2}$. Then it becomes the series given in equation 3.

$ \Rightarrow $So, series given in equation 3 is the expansion of ${\left( {1 - \dfrac{2}{3}} \right)^{\dfrac{{ - 3}}{2}}} = {\left( {\dfrac{1}{3}} \right)^{\dfrac{{ - 3}}{2}}} = {\left( 3 \right)^{\dfrac{3}{2}}} = 3\sqrt 3 $.

$ \Rightarrow $So, $y = 3\sqrt 3 $

$ \Rightarrow $Hence, the value of the given series will be ${\text{3}}\sqrt 3 $.

Note:- Whenever we came up with this type of problem then try to

manipulate the series into the expansion of a known function and then we can

the series in terms of that function. As this will be the easiest and efficient way

to find the solution to the problem.

As, we are given with the series

$ \Rightarrow y = 2 + \dfrac{5}{{2!.3}} + \dfrac{{5.7}}{{3!{{.3}^2}}} + \dfrac{{5.7.9}}{{4!{{.3}^3}}} + ......$ (1)

So, the series at equation 1 can be written as,

$ \Rightarrow y = 1 + 1 + \dfrac{5}{{2!.3}} + \dfrac{{5.7}}{{3!{{.3}^2}}} + \dfrac{{5.7.9}}{{4!{{.3}^3}}} + ......{\text{ }}$ (2)

Now, we know that when we had to find the value of any typical series,

Then we try to manipulate the series into the expansion of a known function.

So, we had to manipulate the series at equation 2.

Above series can be manipulated as,

$ \Rightarrow y = 1 + \dfrac{3}{2}.\dfrac{2}{3} + \dfrac{{\dfrac{3}{2}.\dfrac{5}{2}}}{{2!}}.\dfrac{{{2^2}}}{{{3^2}}} + \dfrac{{\dfrac{3}{2}.\dfrac{5}{2}.\dfrac{7}{2}}}{{3!}}.\dfrac{{{2^3}}}{{{3^3}}} + \dfrac{{\dfrac{3}{2}.\dfrac{5}{2}.\dfrac{7}{2}.\dfrac{9}{2}}}{{4!}}.\dfrac{{{2^4}}}{{{3^4}}} + ......$ (3)

Now, as we know that the expansion of ${\left( {1 + x} \right)^n}$, where n is negative is,

$ \Rightarrow {(1 + x)^n} = 1 + \dfrac{n}{{1!}}x + \dfrac{{n(n - 1)}}{{2!}}{x^2} + \dfrac{{n(n - 1)(n - 2)}}{{3!}}{x^3} + ....$

As, we can see clearly that in the expansion of ${(1 + x)^n}$,

$ \Rightarrow $If we put $x = \dfrac{{ - 2}}{3}$ and ${\text{ }}n = \dfrac{{ - 3}}{2}$. Then it becomes the series given in equation 3.

$ \Rightarrow $So, series given in equation 3 is the expansion of ${\left( {1 - \dfrac{2}{3}} \right)^{\dfrac{{ - 3}}{2}}} = {\left( {\dfrac{1}{3}} \right)^{\dfrac{{ - 3}}{2}}} = {\left( 3 \right)^{\dfrac{3}{2}}} = 3\sqrt 3 $.

$ \Rightarrow $So, $y = 3\sqrt 3 $

$ \Rightarrow $Hence, the value of the given series will be ${\text{3}}\sqrt 3 $.

Note:- Whenever we came up with this type of problem then try to

manipulate the series into the expansion of a known function and then we can

the series in terms of that function. As this will be the easiest and efficient way

to find the solution to the problem.

Recently Updated Pages

what is the correct chronological order of the following class 10 social science CBSE

Which of the following was not the actual cause for class 10 social science CBSE

Which of the following statements is not correct A class 10 social science CBSE

Which of the following leaders was not present in the class 10 social science CBSE

Garampani Sanctuary is located at A Diphu Assam B Gangtok class 10 social science CBSE

Which one of the following places is not covered by class 10 social science CBSE

Trending doubts

Which are the Top 10 Largest Countries of the World?

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

How do you graph the function fx 4x class 9 maths CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Why is there a time difference of about 5 hours between class 10 social science CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE